Opportunities and Risks of Globalization in Rural Areas. Case Study: Botosani County - Maria-Simona Cuciureanu (CES Working Papers, 2014)
The global economy plays an important role in the development of a region or a county/district as it promotes the exploitation of resources and space in a logical and rational manner. The trend of global economic uniformity allows opportunities and risks to Botosani County since globalization involves economic development and rising living standards, but loss of cultural values, traditions and customs. The area of study currently confronts with socio-economic and demographic changes that may be addressed by globalization, but at the same time spatial development according to global standards will cause the loss of Botosani County's authenticity.
Keywords: O18; R00; A10; 330; globalization; economics; opportunities; risk; investment; economics; rural area; rural development